Academic Achievement Among Juvenile Detainees. (July 2015) - Grigorenko, Elena L.; Macomber, Donna; Hart, Lesley; Naples, Adam; Chapman, John; Geib, Catherine F.; Chart, Hilary; Tan, Mei; Wolhendler, Baruch; Wagner, Richard
The literature has long pointed to heightened frequencies of learning disabilities (LD) within the population of law offenders; however, a systematic appraisal of these observations, careful estimation of these frequencies, and investigation of their correlates and causes have been lacking. Here we present data collected from all youth (1, 337 unique admissions, mean age 14.81, 20.3% females) placed in detention in Connecticut (January 1, 2010–July 1, 2011). All youth completed a computerized educational screener designed to test a range of performance in reading (word and text levels) and mathematics. A subsample ( n = 410) received the Wide Range Achievement Test, in addition to the educational screener. Quantitative (scale-based) and qualitative (grade-equivalence-based) indicators were then analyzed for both assessments. Results established the range of LD in this sample from 13% to 40%, averaging 24.9%. This work provides a systematic exploration of the type and severity of word and text reading and mathematics skill deficiencies among juvenile detainees and builds the foundation for subsequent efforts that may link these deficiencies to both more formal, structured, and variable definitions and classifications of LD, and to other types of disabilities (e.g., intellectual disability) and developmental disorders (e.g., ADHD) that need to be conducted in future research.